2018
DOI: 10.1590/1414-431x20177033
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac protein expression patterns are associated with distinct inborn exercise capacity in non-selectively bred rats

Abstract: In the present study, we successfully demonstrated for the first time the existence of cardiac proteomic differences between non-selectively bred rats with distinct intrinsic exercise capacities. A proteomic approach based on two-dimensional gel electrophoresis coupled to mass spectrometry was used to study the left ventricle (LV) tissue proteome of rats with distinct intrinsic exercise capacity. Low running performance (LRP) and high running performance (HRP) rats were categorized by a treadmill exercise test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…According to the methods from literatures[11], a little change is made.At 2 days after training, the load and movement of the rats were increased. The following protocol was applied: running at approximately 5 m/min, 10 min after warming up, followed by a starting load at 10 m/min, with a gradual increase over 3 min, followed by 5 m/min, until exhaustion.…”
Section: Methodsmentioning
confidence: 99%
“…According to the methods from literatures[11], a little change is made.At 2 days after training, the load and movement of the rats were increased. The following protocol was applied: running at approximately 5 m/min, 10 min after warming up, followed by a starting load at 10 m/min, with a gradual increase over 3 min, followed by 5 m/min, until exhaustion.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the cardiac muscle, it has been shown that the basal level of HSPB5 protein is higher in the heart of rats with low running performance, associated with an increase of other proteins related to stress response [ 150 ], while the only paper specifically addressing the exercise-induced modulation of HSPB5 shows that acute endurance exercise does not determine any early upregulation of this protein in mouse heart [ 63 ].…”
Section: Hspb5 Modulation By Physical Activity/exercisementioning
confidence: 99%